Composite cement producing process with flyash in great mixed amount - ZHONGXIN CHEN (2004)
The present invention is composite cement producing process with flyash in great mixed amount, and aims at solving the problems of flyash to occupy land and pollute environment, cement production of Portland cement clinker to produce great amount of CO2 and have high cost, etc. The composite cement producing process includes producing flyash polymerizing material with flyash, grinding assistant,calcium nitrate, caustic soda and anhydrous sodium sulfate and through grinding; crushing clinker; and producing cement product with clinker, flyash, gypsum, flyash polymerizing material and mineral slag. Using great amount of flyash in producing cement can reduce environmental pollution and lower cement producing cost. 一种大掺量粉煤灰生产复合水泥的方法，主要解决粉煤灰排放量大，占用耕地，污染环境，同时生产硅酸盐水泥熟料向大气中排放大量二氧化碳，成本也比较高等问题。本发明的工艺方法是：首先生产粉煤灰聚合料，投入的配方原料重量百分比例是：粉煤灰55-68、助磨剂15-25、硝酸钙2-7、火碱2-7、无水硫酸钠3-8，将这些原料入磨，磨制超细粉状；将熟料破碎，予粉磨入仓；将下述配方按重量百分比例混合入磨粉磨成产品：予粉磨熟料45-55，粉煤灰35-45，石膏2-4，粉煤灰聚合料1-1.5，矿渣5-7。优点是能大量利用粉煤灰，减少了粉煤灰对环境的污染；对粉煤灰进行了两次定向聚合处理，节约了水泥熟料、降低生产成本。